(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The tort of malicious prosecution is intended to shield people from unjustified lawsuits brought with the intention of causing harm. The doctrines application in India and the US is compared in this study with an emphasis on the key components judicial interpretations and available legal remedies in each country. The tort has developed differently in each legal system despite its origins in English common law. In India as well as the U. S. s. three essential components must be proven by the claimant: the lack of probable cause malice and a successful conclusion of the initial action. Nonetheless there are notable differences between the two nations legal systems and constitutional protections for victims of malicious prosecution. Particularly under the Fourth and Fourteenth Amendments which shield people from infringements on their personal freedom the United States incorporates constitutional protections into the framework for malicious prosecution. Under Section 1983 of the U. S. s. Code also gives victims a way to file a claim for constitutional violations which frequently results in both punitive and compensatory damages. In contrast Indian law treats malicious prosecution primarily as a tort claim with limited constitutional dimensions. Punitive damages are infrequently granted even though Article 21 of the Indian Constitution shields people from capricious acts. Instead compensatory damages are the norm for remedies. This essay emphasizes the wider safeguard provided by the U. S. s. superior to the more conservative stance adopted by Indian courts due to the legal systems constitutional framework and the availability of punitive damages. The comparative analysis demonstrates the importance of malicious prosecution in maintaining the integrity of judicial processes while emphasizing the need for legal systems to balance the rights of complainants and defendants effectively.